Avaliação de compostos modelos visando propor um método de diferenciação de matéria orgânica lábil e recalcitrante em ambientes aquáticos - Constantino, Isabela Carreira [UNESP] (2015)
The development of a method which allows to differentiate the labile fraction of recalcitrant organic matter is critical for the interpretation of environmental processes in aquatic environments. The purpose of this study was to evaluate the use of kinetics of consumption of H2O2 in the presence of models compounds of organic matter in order to propose a lability indicator of organic matter for natural water. For this, experiments were conducted in microcosms with water and different concentrations of compounds models of organic matter (humic acid, fulvic acid, lignin, sodium pyruvate and ascorbic acid). The microcosms were studied in a system with reactors with cooling jacket, which received known amount of H2O2 (7.1 mmol L-1) and the temperature and pH controlled throughout the experiment. A microcosm control was assembled containing only water and H2O2. At intervals of time calculated in accordance with the kinetics of the decrease of concentration of H2O2 quantification was performed using the photometric method of the sulphate of N,N -diethylp- phenylethylenediamine. Parameters such as total organic carbon and iron (II) were quantitated using Total Organic Carbon Analyzer and method of orthophenanthroline, respectively, at the beginning and end of the experiments. The characterization of the samples was carried out using the techniques of Molecular Spectroscopy Fluorescence and UV -Vis. Mathematical models were applied to determine the reaction order and their respective halflives for the kinetics of consumption of H2O2. Lignin and fulvic acid were the best compounds that are suited as compounds of recalcitrant organic matter, as in kinetic studies, the results for the half-lives of H2O2 had their values close to those obtained for the control experiments (75.3 and 69.2 hours ), indicating that H2O2 oxidation did not act on these compounds. For the experiment using sodium pyruvate, the H2O2...